Uji Kuat Tekan dan Uji Kuat Tarik Beton Dengan Agregat Kasar dan Halus dari Sumba Barat Daya pada Mutu Beton = 19,3 MPa - Lolo , Wilfridus Muri ; Karjanto , Adjib; Ningrum, Diana (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
The use of fine aggregates and coarse aggregates in Southwest Sumba Regency as composers of concrete mixes for construction work in general is still dependent on sea sand and natural gravel (mountain rocks) whose potential is quite large. This research aims to; 1) knowing the characteristics of sea sand and natural gravel (mountain rocks) of West Sumba 2) knowing the compressive strength of concrete and tensile strength produced from sea sand and natural gravel (mountain rocks) Southwest Sumba; This study is a sample-based laboratory study and analysis of the characteristics of aggregate and compressive tests. Southwest Sumba aggregates generally meet the requirements for testing aggregate characteristics. Southwest Sumba sea sand with equipment modulus 3,214 and entering zone 2 (sand somewhat coarse) and coarse aggregate (Southwest Sumba gravel) with fineness modulus 4.65 and entering zone.40 mm. The highest compressive strength of concrete from the age of the concrete to the end is obtained from Southwest Sumba sea sand with a compressive strength of 17,486 MPa (7 days concrete age), 26,901 MPa (28 days concrete age).